The Theory of Planned Behavior Approach to Enhancing Purchase Intention of Environmentally Friendly Electronic Products Amid the Electronic Waste Crisis - Fivi Ermaningsih; Yolanda Masnita (Universitas KH. Abdul Chalim Mojokerto, 2025)
Green marketing is a strategic approach that emphasizes the importance of sustainability and environmental awareness in marketing activities. One of the pressing issues driving the urgency of this approach is the increasing amount of electronic waste, which is projected to exceed 12,000 tons per day in Indonesia by 2030. Although public awareness of environmental issues is rising, purchasing behavior toward eco-friendly products remains low, indicating a gap between attitude and action. This study employs the Theory of Planned Behavior (TPB) framework, modified by the addition of the Ethical Obligation variable, to analyze Purchase Intention toward environmentally friendly electronic products. The model includes five main variables: Subjective Norms, Perceived Behavioral Control, Environmental Concern, Attitude, and Ethical Obligation. The results show that Purchase Intention is influenced by Perceived Behavioral Control and Ethical Obligation, while Subjective Norms and Attitude do not have a positive effect on Purchase Intention. Environmental Concern influences Attitude, but not Purchase Intention directly. This research contributes to strengthening green marketing strategies and promoting sustainable consumer behavior. Recommendations include testing other green products and adding external variables such as price, product availability, and media influence as factors that may enhance the understanding of consumer Purchase Intention.